2020
DOI: 10.2987/19-6876.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hurricane Irma on Our Community and the Collier Mosquito Control District's Mission

Abstract: The Collier Mosquito Control District, located in southwest Florida, is uniquely positioned in a subtropical environment between the Gulf of Mexico and Everglades National Park. The District's mission is focused on the control of disease vector and nuisance mosquitoes in Collier County, which is accomplished through integrated mosquito management. Hurricane Irma made landfall in the county on September 10, 2017, leaving in its wake tremendous property and infrastructure damage, and it also disrupted communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Resources dedicated to addressing VBD have a history of being shunted during times of competing disasters [ 20 ]; however, some natural disasters may create favorable conditions for increased abundance of vectors [ 33 , 34 ], thus generating cyclical and often regional disparities in funded vector-control efforts. Funding increases post-Hurricanes Matthew, Irma and Harvey serve as examples [ 20 , 35 , 36 ]. The current needs assessment survey corresponded with the COVID-19 pandemic and shed light on vector control needs during a competing emerging public health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Resources dedicated to addressing VBD have a history of being shunted during times of competing disasters [ 20 ]; however, some natural disasters may create favorable conditions for increased abundance of vectors [ 33 , 34 ], thus generating cyclical and often regional disparities in funded vector-control efforts. Funding increases post-Hurricanes Matthew, Irma and Harvey serve as examples [ 20 , 35 , 36 ]. The current needs assessment survey corresponded with the COVID-19 pandemic and shed light on vector control needs during a competing emerging public health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tropical cyclones caused > 7000 houses to collapse and 350,000 people to urgently relocate in Guangdong Province in 2014 [ 40 ], which may have contributed to the anomalous dengue epidemic. Another study conducted in southwest Florida showed that the lengthy loss of electrical power after Hurricane Irma forced most residents outdoors, increasing their exposure to mosquitoes [ 41 ]. In addition, the heavy rainfall carried by tropical cyclones might provide a conducive environment for mosquito breeding.…”
Section: Discussionmentioning
confidence: 99%